Rosiglitazone Enhances Apolipoprotein M (Apom) Expression in Rat's Liver - Luo, Guanghua (Ivyspring International Publisher, 2014)
Apolipoprotein M (APOM) has been suggested as a vasculoprotective constituent of high density lipoprotein (HDL), which plays a crucial role behind the mechanism of HDL-mediated anti-atherosclerosis. Previous studies demonstrated that insulin resistance could associate with decreased APOM expressions. In agreement with our previous reports, here, we further confirmed that the insulin sensitivity was also reduced in rats treated with high concentrations of glucose; such effect could be reversed by administration of rosiglitazone, a peroxisome proliferator-activated receptor-γ (PPARγ). The present study shows that Apom expression is significantly affected by either rosiglitazone or hyperglycemia alone without cross interaction with each other, which indicates that the pathway of Apom expression regulating by hyperglycemia might be differed from that by rosiglitazone. Further study indicated that hyperglycemia could significantly inhibit mRNA levels of Lxrb (P=0.0002), small heterodimer partner 1 (Shp1) (P<0.0001), liver receptor homologue-1 (Lrh1) (P=0.0012), ATP-binding cassette transporter 1 (Abca1) (P=0.0012) and Pparb/d (P=0.0043). Two-way ANOVA analysis demonstrated that the interactions between rosiglitazone and infusion of 25% glucose solution on Shp1 (P=0.0054) and Abca1 (4E, P=0.0004) mRNA expression was statistically significant. It is concluded that rosiglitazone could increase Apom expression, of which the detailed mechanism needs to be further investigated. The downregulation of Apom by hyperglycemia might be mainly through decreasing expression of Pparg and followed by inhibiting Lxrb in rats.